Environmental and social impacts of infrastructure development in East Africa - Roque de Pinho, Joana (Proceedings of the Silk Roads Conference: Anticipating Social and Environmental Impacts of China’s Belt and Road Initiative in the Mountains of Central Asia, 2018)
Many megaprojects are underway within development corridors in Africa, focused on mineral and oil extraction, along with auxiliary infrastructure developments; including Kenya’s Standard Gauge Railway project, the largest postindependence project. 2. East African savannah ecosystems and local livelihoods are highly vulnerable to habitat fragmentation from linear infrastructure, especially due to the importance of mobility for both migratory wildlife and livestock. 3. Independent EIAs and free, prior and informed consent (FPIC) from local communities is necessary to reduce social and environmental impacts. 4. New linear infrastructure should be located where costs are smaller, in highly settled areas with high agricultural potential, and built with mitigating infrastructure to avoid ecosystem fragmentation.